Dynamic and Static Behavior of E–E' Bonds in Neutral and Charged Forms of HEE'H, MeEE'Me, and Cyclo‐1, 2‐EE'(CH2)3 (E, E' = O, S, Se, and Te) Elucidated by AIM Dual Functional Analysis. Issue 5 (24th June 2014) - Hayashi, Satoko; Matsuiwa, Kohei; Miza, Hiroaki; Nakanishi, Waro
ABSTRACT The nature of the E‐*‐E' bonds in neutral, monoanionic, monocationic, and dicationic forms of HEE'H (1), MeEE'Me (2), and cyclo‐1, 2‐EE'(CH2)3 (3) (E, E' = O, S, Se, Te) is investigated by applying AIM (atoms‐in‐molecules method) dual functional analysis. Hb(rc) are plotted versus Hb(rc) – Vb(rc)/2 for the data of E‐*‐E' at bond critical points (BCPs) of fully optimized structures and perturbed structures around the fully optimized ones. Plots for the fully optimized structures are analyzed by the polar coordinate (R, θ) representation. The (θp, κp) parameters are derived from those of the perturbed structures: θp corresponds to the tangent line of each plot, and κp is the curvature. While (R, θ) correspond to the static nature, (θp, κp) represent the dynamic nature of interactions. The nature of E‐*‐E' in the neutral and charged species is classified by comparing their θ and θp values with those of the standard interactions as a reference. Data for E‐*‐E' in the neutral forms of 1–3 appear in the shared‐shell (SS) region (180° < θ), except for MeS‐*‐TeMe (2c), which does in the regular closed‐shell (CS) region (90° < θ < 180°). The E–E' bonds in the monoanionic forms of 1–3 become much longer and weakened. Therefore, data of the monoanionic forms appear in the regular CS. On the other hand, the strengths of E‐*‐E' in the mono‐ and dicationic forms are almost equal to those in the neutral forms of 1–3 in the plots, irrespective of the shorter E‐*‐E' lengths in the cationic forms, relative to the neutral forms.